Influence Of 5% Coconut Shell As Partial Replacement Of Fine Aggregate Added In Concrete Towards Workability - Nur Zulaiha, Saruddin (2023)
Most countries face problems to dispose of plant waste including Malaysia. In addition, the increase in discarded coconut shells is increasing and it is important to find alternatives to solve this problem. One of the solution is to use coconut shell waste as a building material. Construction is a sector that sustains development growth while consuming large amounts of materials. Therefore, it acts as a potential route to recycle coconut shell waste even though the use and consumption of coconut shell waste is currently low in Malaysia. This study seeks to attempt to use coconut shell waste (plant waste) to replace a certain amount of fine aggregate in the concrete mix with weight reduction. For this, two mixture compositions of varying conditions according to suitability with 5% coconut shell waste were prepared and tested in two conditions, mainly the fresh workability test, and the fresh compression test. Furthermore, normal concrete poured without the inclusion of residual shell acts as a parameter for the comparison of property changes between mixes. The results show that concrete incorporating fine aggregates has lower workability and exhibits a significant reduction in concrete workability. The accuracy of the data is less accurate in the slump test due to the quantity of material used being insufficient by 20% when making the CMD calculation. Finally, the compaction factor test showed a 30% increase in the slump cone test. In fact, the difference in the preparation of ingredients is mainly the coconut shell.